The Existence of a Stay Period in Bankruptcy That Begins with Postponement of Debt Payment Obligations (PKPU) - Aliya Sandra Dewi; Yuhelson; Dewi Anggraeni (International Journal of Scientific Multidisciplinary Research, 2024)
In reference to bankruptcy and PKPU, Article 290 of Law No. 37 of 2004 is in conflict with the existence of Supreme Court Circular Letter Number 5 of 2021. This study tackles the problem of putting the stay period in place for the execution of collateral in bankruptcy, which results from the refusal of peace in the form of deferring debt payments. It also looks at the stay period that surrounds collateral execution in bankruptcy and its implications for potential changes to the Bankruptcy Law in the future. The Contractarian Approach Theory serves as the Applied Theory, Bankruptcy Law Theory as the Middle Range Theory, and Legal Certainty Theory as the Grand Theory in this study. It employs a normative juridical research methodology with a statutory approach as its main focus. This method entails looking at and dissecting Law No. 37 of 2004's provisions regarding PKPU and bankruptcy. Secondary data, comprising primary, secondary, and tertiary legal materials, is the type of data utilized. Qualitative juridical analysis is used in the data analysis. According to Since there is no regulation regarding the suspension period for debtors declared bankrupt due to the Panel of Judges' rejection of a postponement of debt payment obligations, the theory of legal certainty has not been satisfied by the provisions regarding the suspension period (stay period) in Article 56, paragraph (1) of Law No. 37 of 2004 concerning Bankruptcy and PKPU